2022
DOI: 10.1186/s12909-022-03888-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antenatal point-of-care ultrasound training workshops for rural/remote healthcare clinicians: a prospective single cohort study

Abstract: Background There is limited access to life-saving antenatal ultrasound in low-resource rural and remote settings worldwide, including Australia, mainly due to shortages in skilled staff. Point-of-care ultrasound (PoCUS) offers a viable solution to this service deficit, however, rural clinicians face many barriers accessing training and professional development critical to advancing their clinical practice. Standards for PoCUS training and competency assessment are unclear. Regulation is lacking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…For midwives, participation in continuing education courses on ultrasound diagnostics represents a significant enhancement of their ultrasonographic skills and knowledge, augmenting their existing clinical competencies [ 19 ]. Throughout the duration of these training courses, midwives are either relieved from their clinical responsibilities or they undertake the training concurrently with their standard duties [ 17 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For midwives, participation in continuing education courses on ultrasound diagnostics represents a significant enhancement of their ultrasonographic skills and knowledge, augmenting their existing clinical competencies [ 19 ]. Throughout the duration of these training courses, midwives are either relieved from their clinical responsibilities or they undertake the training concurrently with their standard duties [ 17 , 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Geographic challenges, including extensive distances and inadequate transportation infrastructure, compound the difficulty of accessing obstetric care, imposing economic burdens [ 17 ]. These regions are further characterized by a significant dearth of trained personnel and insufficient resources for hospitalization, alongside deficiencies in antenatal care and elevated rates of maternal and fetal mortality [ 17 , 20 ]. In LMICs, congenital anomalies account for approximately 5–7% of perinatal mortality rates, suggesting that improved access to obstetric ultrasound could enhance the detection of high-risk conditions and improve maternal and neonatal outcomes [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The goal of POCUS is to transfer some of the basic ultrasound skills to non-imaging health professionals such that these skills assist them in making clinical decisions to manage their patients. This also addresses the critical shortage of imaging professionals in many settings especially low income settings [ 4 ]. In this study, the midwives demonstrated minimal decrease in knowledge even at 6 months follow up as can be evidenced in the exam scores.…”
Section: Discussionmentioning
confidence: 99%